Assessing the validity of maternal report on breastfeeding counselling in Kosovo’s primary health facilities - McKay, Melinda; Munos, Melinda K.; Kim, Sunny S.; Bryce, Emily; Bucina, Hana; Marchant, Tanya (BioMed Central, 2024)
Background Improving the quality of breastfeeding counselling delivered by primary care providers can improve breastfeeding outcomes and ultimately reduce mortality and morbidity of children and mothers. Accurate data on coverage and quality of primary care breastfeeding counselling is essential for monitoring progress; however, global and national indicators are limited. To help address this gap, this study validated indicators of receipt and quality of breastfeeding counselling during routine consultations for infant care at seven primary health facilities across Kosovo.